2005
DOI: 10.1523/jneurosci.4555-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Specific Knock-Out of Hypoxia-Inducible Factor-1α Reduces Rather Than Increases Hypoxic-Ischemic Damage

Abstract: Hypoxia-inducible factor-1␣ (HIF-1␣) plays an essential role in cellular and systemic O 2 homeostasis by regulating the expression of genes important in glycolysis, erythropoiesis, angiogenesis, and catecholamine metabolism. It is also believed to be a key component of the cellular response to hypoxia and ischemia under pathophysiological conditions, such as stroke. To clarify the function of HIF-1␣ in the brain, we exposed adult mice with late-stage brain deletion of HIF-1␣ to hypoxic injuries. Contrary to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
173
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(188 citation statements)
references
References 31 publications
14
173
1
Order By: Relevance
“…The possible differential roles of HIF-1 in different cell types may provide partial explanations for the divergent results from different groups. In our study, as well as the study by Helton et al (Helton et al, 2005), HIF-1α inhibition involved neuronal as well as non-neuronal cell types in the CNS, which may result in an overall pathological role for HIF-1α. Therefore, it is possible that the benefits of blocking HIF-1α across non-neuronal cell types outweigh the potential negative side effects of neuron specific HIF-1α blockade.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The possible differential roles of HIF-1 in different cell types may provide partial explanations for the divergent results from different groups. In our study, as well as the study by Helton et al (Helton et al, 2005), HIF-1α inhibition involved neuronal as well as non-neuronal cell types in the CNS, which may result in an overall pathological role for HIF-1α. Therefore, it is possible that the benefits of blocking HIF-1α across non-neuronal cell types outweigh the potential negative side effects of neuron specific HIF-1α blockade.…”
Section: Discussionsupporting
confidence: 80%
“…Recent reports have suggested that HIF-1α inhibition after cerebral ischemia imparts neuroprotection in adult experimental models (Chang et al, 2007;Chen et al, 2007). A study of brain-specific knockouts of HIF-1α in mice after hypoxic injury suggested that HIF-1α is implicated in brain damage and decreasing the level of HIF-1α could be neuroprotective (Helton et al, 2005). Thus, HIF-1α seems to be capable of playing a dual role by activating both pro-death and anti-apoptotic pathways (Chang et al, 2007;Chen et al, 2007;Baranova et al, 2007;Helton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxiainducible factor-1a has an essential role in cellular and systemic oxygen homeostasis by regulating the expression of genes important in glycolysis, erythropoiesis, angiogenesis, and catecholamine metabolism (Semenza, 2010). Hypoxia-inducible factor-1a-deficient mice were protected from hypoxia-induced cell death, suggesting that decreasing the level of HIF-1a can be neuroprotective (Helton et al, 2005). Under conditions of low oxygen, HIF-1a accumulation leads to the expression of the fur gene and transcription of the protein, Furin, which activates MMP-14, resulting in the activation of the constitutive enzyme, MMP-2 (Figure 3).…”
Section: Neuroimaging Of the Neurovascular Unitmentioning
confidence: 99%
“…For example, two groups used the same murine model to invalidate HIF-1␣ expression in neurons (floxed HIF-1 mice crossed with CAM-Cre mice (Cre recombinase under the control of the calcium calmodulindependent kinase promoter)). They observed opposite effects after hypoxia or ischemia: a deleterious or a protective effect of HIF-1␣ expression for neuronal survival (Helton et al, 2005;Baranova et al, 2007). There may be several reasons for this difference in findings.…”
Section: Discussionmentioning
confidence: 99%